Being plurilingual versus becoming a linguistically sensitive teacher: tensions in the discourse of initial teacher education students. Issue 4 (2nd October 2021) - Birello, Marilisa; Llompart-Esbert, Júlia; Moore, Emilee
ABSTRACT: The beliefs of pre-service teachers in initial teacher education (ITE) in Catalonia about plurilingualism and teaching in diverse classrooms are analysed and tensions in their discourse are observed. Following the analysis of discourse in interaction (e.g. Heller [2005]. Discourse and interaction. In D. Schiffrin, D. Tannen, & H. E. Hamilton (Eds.), The handbook of discourse analysis (pp. 250–264). Blackwell Publishers Ltd), we analyse data from an individual reflection task and subsequent focus group discussion in which pre-service teachers discuss their ideas about linguistically sensitive teaching. Our findings suggest that pre-service teachers have very positive ideas regarding being plurilingual speakers. However, when positioning themselves as teachers, the feelings they express about linguistic diversity in schools become negative. These ideas are linked to ideological constructions that circulate, for example, in European institutional discourses about multi/plurilingualism and in neoliberal conceptions of languages and learning. We suggest that more spaces for discussion and reflection are needed in ITE in order to promote linguistically sensitive teaching among future practitioners.